Synergistic effect of regenerating agent plus cord blood serum eye drops for the treatment of resistant neurotrophic keratitis: a case report and a hypothesis for pathophysiologic mechanism - Giannaccare, Giuseppe (Int Med Case Rep J, 2015)
This report describes a case of a 72-year-old Caucasian woman presenting with a large neurotrophic keratitis with a large persistent epithelial defect, with a longest linear diameter of 7 mm and greatest perpendicular width of 5 mm, affecting epithelium, Bowman membrane, and anterior stroma. Corneal disease was resistant to conventional treatment and classified as stage 2 according to Mackie classification. Patient was instructed to instill regenerating agent (RGTA) eye drops in the morning, as the first eye drop, once every 5 days in combination with daily cord blood serum (CBS) eye drops 6 times/day. The patient was asked to visit after 1 week (V1), 2 weeks (V2), 3 weeks (V3), and 4 weeks (V4) of study treatment. In V4 treatment, corneal sensitivity improved, and keratitis healed with resolution of stromal inflammation. Global treatment tolerance was very satisfactory. Patient continued the therapy for a further month after complete healing. Currently, the patient has been followed up for 3 months without any sign of keratitis recurrence. To the best of our knowledge, this case report describes for the first time the successful combined use of RGTA and CBS eye drops for the treatment of neurotrophic keratitis resistant to conventional treatment. We hypothesize that RGTA eye drops could provide an optimal migration substrate and that growth factors supplied by CBS eye drops could strengthen the repair process by promoting cell growth over the matrix. Combined RGTA and CBS eye drop therapy could be a new potential option for the successful treatment of resistant neurotrophic keratitis, particularly when each drug alone is not effective.